2019
DOI: 10.1080/15384101.2019.1632133
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Up-regulated microRNA-199b-3p represses the apoptosis of cerebral microvascular endothelial cells in ischemic stroke through down-regulation of MAPK/ERK/EGR1 axis

Abstract: MicroRNAs (miRNAs) have emerged as key mediators of posttranscriptional gene silencing in both pathogenic and pathological aspects of ischemic stroke biology. Therefore, the purpose of present study was to explore the effect of microRNA-199b-3p (miR-199b-3p) on the cerebral microvascular endothelial cells (CMECs) in middle cerebral artery occlusion-reperfusion (MCAO-R) mice by regulating MAPK/ERK/EGR1 axis. Mice were used to establish MCAO-R models and to measure the expression of miR-199b-3p and the MAPK/ERK/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…In addition to cancer, hsa-miR-199b-3p plays an important role in other diseases. The apoptosis of cerebral microvascular endothelial cells was repressed via upregulation of hsa-miR-199b-3p in ischemic stroke [ 28 ]. Wu et al showed that hsa-miR-199b-3p was substantially increased in extracellular vesicles from the nasal mucus of patients with allergic rhinitis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cancer, hsa-miR-199b-3p plays an important role in other diseases. The apoptosis of cerebral microvascular endothelial cells was repressed via upregulation of hsa-miR-199b-3p in ischemic stroke [ 28 ]. Wu et al showed that hsa-miR-199b-3p was substantially increased in extracellular vesicles from the nasal mucus of patients with allergic rhinitis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCR quantification was performed as previously described [ 26 ]. To test miRNA expression, we used stem-loop qRT-PCR for miR-199a-3p, miR-199b-3p, and miR-758-3p following the protocol described previously [ 27 , 28 ]. Primers are shown in Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…MiRNA-210 induces the apoptosis of neuronal cells of mouse model with cerebral ischemia by activating the HIF-1α-VEGF pathway [ 25 ]. Upregulation of miRNA-199b-3p effectively suppresses the apoptosis of cerebral microvascular endothelial cells in ischemic stroke by modulating the MAPK/ERK/EGR1 axis [ 26 ]. These evidences all demonstrates that miRNAs are closely involved in the development of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…qPCR quantification was performed by using the TB Green® Fast qPCR Mix (TaKaRa) according to the manufacturer's manual on the ABI-7500 (Applied Biosystems). For testing miRNA expression, stem-loop qRT-PCR was used referring to others' work [ 23 , 24 ]. Primers are shown in Table S1 .…”
Section: Methodsmentioning
confidence: 99%